Integration – An Outline from the Perspective of the Sociology of Knowledge - Soeffner, Hans-Georg; Zifonun, Dariuš (Qualitative Sociology Review, 2008)
In this conceptual essay we argue that the study of migration can substantially benefit from an interactionist notion of integration. Basing our considerations on Berger’s and Luckmann’s sociology of knowledge, we develop a differentiated understanding of integration as an ongoing process which comes to be institutionalized in characteristic forms. With regard to these forms of institutionalization, we focus our attention on the relatively stable spheres of social action characterized by Anselm Strauss as social worlds, structures that are continuously produced anew and altered through processes of segmentation, intersection and legitimation. Furthermore, we propose five ideal types of social worlds reflecting the perspective of migrants. In addition, we indicate the transnational scope of social worlds and the importance of personal coping strategies. We emphasize the significance of the conflicts occurring in and between social worlds as part of processes of integration and highlight a number of strategies that make symbolic integration within the public sphere possible. Furthermore, we list central institutionalized cultural forms and social modes which have a decisive impact on interaction between migrants and the autochthonous population: categorization, stereotyping and drawing boundaries, negotiating, conflict and permanent reflection. Finally, we explain the specific contribution our approach offers to the current theoretical discussion in the field of migration studies and close with a summary of our arguments.